Life satisfaction in the context of the COVID-19 pandemic among middle school adolescents in France: findings from a repeated cross-sectional survey (EnCLASS, 2012–2021) - Hurel, Cynthia; Ehlinger, Virginie; Molcho, Michal; Cohen, Jérémie F.; Falissard, Bruno; Sentenac, Mariane; Godeau, Emmanuelle (Frontiers in Pediatrics, 2023)
Background and aims: Since the COVID-19 pandemic, several studies have reported a decrease in adolescents' well-being. We aim to describe life satisfaction over the last decade and examine the factors associated with its variations between 2020 and 2021 among French students in their last year of middle school (around 14-15 years old). Methods: Data were drawn from a repeated biennial cross-sectional national survey conducted in French schools over the last decade (EnCLASS study), using a self-administered questionnaire. After describing life satisfaction trends between 2012 and 2021 using the Cantril ladder, we examined individual changes in life satisfaction between 2020 and 2021 and their associations with housing and studying conditions during the COVID-19 lockdown, using multinomial logistic regression analysis (decrease, increase, no change as reference). Results: Among the 17,686 survey respondents, an overall slight decrease in the prevalence of adolescents reporting high life satisfaction (i.e., Cantril score ≥6) was observed since 2012 with the lowest proportion reported in 2021 (77.4%). Between 2020 and 2021, 16.3% of French adolescents experienced an improvement in life satisfaction, while 17.7% experienced the opposite. Decrease in life satisfaction between 2020 and 2021 was more likely experienced by adolescents living in reconstructed families (aOR 2.09 [95%CI 1.58-2.77]), those who did not have their own room (aOR 1.58 [1.16-2.15]), nor access to the Internet to interact with their friends during the lockdown (aOR 1.47 [1.09-1.98]). Interestingly, more girls than boys were represented in both those reporting increase and decrease in life satisfaction (aOR 1.82 [1.40-2.37] and 1.43 [1.14-1.79], respectively). Conclusions: This study shows that the way adolescents experienced the first 2020 lockdown in France was not uniform, and that one must consider sex as well as housing and studying conditions when interpreting adolescents’ life satisfaction decrease during the COVID-19 pandemic.